Garden of Mentoring: Revisiting Mentoring in Entrepreneurial Sense - Teraman, Seray Begüm Samur; Ergun, Hande Sinem (My University, 2016)
For many years, mentoring has been used as the influential career development tool in organizations. From a wider perspective, mentoring is perceived as a way of people development by helping individuals to achieve something meaningful in their lives. However, due to proliferation of entrepreneurial initiatives, now it is not only scrutinized from an intra-organizational perspective, but also it is considered a tool for self-employed development. Therefore, new area for cultivation in the garden of mentoring has emerged: Entrepreneurial Mentoring. Although, its multi-faceted development effect for new ventures is accepted, mentoring is not highly discussed topic in entrepreneurship literature to the best of our knowledge (St-Jean and Mathieu, 2015, St-Jean and Audet,2009). Hence, this conceptual study mainly deals with definitional issues, roots of mentoring and how mentoring evolves from career development towards entrepreneurial development perspective. The concern is offering some insights about multiple roles of mentoring, especially for new-start ventures as a supportive mechanism in their entrepreneurial journey.
Keywords: Mentoring; Entrepreneurial Mentoring; Entrepreneurship; New-Start Ventures; Career Development; Mentorlük; Girişimcilik Mentorluğu; Girişimcilik; Yeni Başlangıç ​​Girişimler; Kariyer Gelişimi